Design of Merchandise Inventory Accounting System at PT. Abdi Karya Kotamobagu - Nadia Mokodompit; Inggriani Elim; Anneke Wangkar (PT FORMOSA CENDEKIA GLOBAL, 2023)
A well-designed accounting system will provide good benefits for management in managing its business. PT. Abdi Karya Kotamobagu is a company operating in the supermarket sector. The aim of this research is to design an inventory accounting system at PT. Abdi Karya Kotamobagu. The research results show that PT. Abdi Karya Kotamobagu has an inventory accounting system that supports company operations, but there are still several problems such as loss of merchandise caused by several parties or incomplete goods received from distributors due to the warehouse not checking the goods received, shortages and excess inventory and vacancies. merchandise inventory. This happens because the documents used regarding inventory have not been designed properly, there is no inventory card function and physical counting system.